The book of Ecclesiastes (Qohelet) and the path to joyous living - Perry, T (Cambridge Cambridge University Press, 2015)
This is the first full-length study of Ecclesiastes using methods of philosophical exegesis, specifically those of the modern French philosophers Levinas and Blanchot. T. A. Perry opens up new horizons in the philosophical understanding of the Hebrew Bible, offering a series of meditations on its general spiritual outlook. Perry breaks down Ecclesiastes' motto 'all is vanity' and returns 'vanity' to its original concrete meaning of 'breath', the breath of life. This central and forgotten teaching of Ecclesiastes leads to new areas of breath research related both to environmentalism and breath control.
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Bible; Bible -- Criticism, interpretation, etc; Bible ; Ecclesiastes ; Criticism, interpretation, etc